F. OTTO, J.M. SONGEL - Frei Otto. Conversaciones con Juan Maria Songel - Colón, Alegría (ZARCH, 2018)
Frei Otto, José María SongelFrei Otto. Conversaciones con Juan Maria SongelEditorial Gustavo Gili, S.L., Barcelona, 2008, 96 páginas. Idioma: castellano. Tapa blanda. 12€.ISBN 978-84-252-2205-4